Fontes e níveis de ferro no crescimento e saúde de tilápia do Nilo (Oreochromis niloticus) - Hermes, Luiza Beatriz (2022)
Iron (Fe) is an extremely important micromineral in the development of animals. The present study aimed to evaluate the zootechnical performance, hematology, innate immunity, biochemical and oxidative parameters of tilapia juveniles (Oreochromis niloticus) fed diets containing levels (60 and 85 mg/kg) and sources (organic and inorganic) of iron. Fish (16.57 ± 2.25 g) were fed three times a day for 7 weeks, fish (400) were distributed in 20 tanks (240 L, 20 fish each). The experiment consisted of 5 treatments, in a completely randomized design: basal diet (DB), without inclusion of Fe in the mineral mixture, 60 inorganic, 60 organic, 85 inorganic and 85 organic. Inclusion of the organic source of Fe in the diet improves the performance of tilapia juveniles. Organic Fe improves relative weight gain (261.34%), final weight (61.73g) and biomass (1254.55%). Somatic digestive index and hepatosomatic index were higher in fish fed with inorganic Fe 85. Tilapia liver glucose and ammonia increase in fish fed organic Fe. Organic Fe improves hematocrit and mean corpuscular hemoglobin. Lysozyme (LZ) values decreased in fish fed with organic Fe, but the hemolytic activity of the complement system (HACS) and the NBT test increased with organic Fe. Fish fed an organic Fe 85 diet showed better antioxidant responses. It was concluded that the inclusion of an organic source of Fe at the 85 mg/kg level is more efficient for Nile tilapia juveniles.